PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DI KAMPUNG PINTARENG KECAMATAN TABUKAN SELATAN TENGGARA - KAEHE, DIRADIMALATA; RURU, JOORIE MARHAEN; ROMPAS, WELSON (Sam Ratulangi University, 2019)
Community participation in development planning is very important for development planning. Becausebasically the planning process for village development cannot be separated from the participation of thecommunity itself. The purpose of this study was to determine community participation in developmentplanning in Pintareng Village. This research uses descriptive qualitative research methods. Datacollection techniques used are observation, interviews and data collection with documents. To see howcommunity participation in development planning in the Pintareng village. The researcher uses threeindicators namely: contribution of ideas, contribution of funds and goods and contribution of personnel.Based on the results of this study stated that community participation in development planning in thePintareng village is still not good, because people are still less aware of the importance of them participatingin development planning. Thus I can be concluded that the awareness of the community in developmentplanning in the Pintareng village is still not good.Keywords: society participation, Development Planning